Microwave-Assisted Deacetylation of Chitin from Shrimp Shells - Zainal Arifin (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
The microwave has been used for various applications of organic synthesis. Microwave was used in this  study in order to transform chitin to chitosan. Theprocess of deacetylation of chitin was done by varying heating time 3, 7, 11, and 15 minutes under of power of 400 W. Two grams of chitin were mixed with 40 mL of NaOH solution 70% in a beaker glass. The mixtureput into the apparatus microwave in constant temperature at 70°C. Chitosan was washed until neutral and then was dried in oven. The Degree of Deacetylation (DD) were analyzed using Fourier Transform Infrared (FTIR) instrument. The results that showed the degree of deacetylation is 85.32% was achieved at reaction time in 15 minutes. The parameters of chitosan such as moisture content, ash content,  and viscosity were obtained 9.23%, 0.16% and 58.05  cP, respectively.